Determination of Ruboxistaurin analysis in rat plasma utilizing LC-MS/MS technique - Bushra T. AlQuadeib; Fadilah S. Aleanizy; Fulwah Y. Alqahtani; Rehab A. Alshammari; Amal Aldarwesh; Ibrahim Alsarra (Elsevier, 2023)
Background: Ruboxistaurin (RBX) used to treat retinopathy in diabetic patients which caused by microvascular damage and leakage which contributes to visual loss. There are no published studies on the use of liquid chromatography-tandem mass spectrometry for development and validation of a simple, sensitive, and accurate method for measuring RBX in rat plasma. Method: Chromatographic separation of RBX was achieved using ultra-performance liquid chromatography. Multiple-reaction monitoring quantification used RBX [M + H] + ion at m/z 469.18 and daughter ions at m/z 84, 58.12, and 98.10. Atorvastatin was used as internal standard (IS), has a single daughter ion, and was identified using m/z 559.6 → 249.9. Validation of the liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for RBX in rat plasma for linearity (greater than0.997) was carried out at 25-1000 ng/mL. Results: In rat plasma, the accuracy was within 3.4%, and the intra- and inter-day precision was within 11.8%. Stability, recovery, and matrix effect were all within acceptable limits. The drug retention time (0.85 ± 0.03 min) was remarkably short. Conclusion: The method developed in the current study is suitable to quantify RBX in plasma or bulk doses.